Ex situ conservation of plants in the Red List of Apulia: preliminary results - Accogli R.; Marchiori S.; Medagli P.; Ippolito F. (Italo-Albanian cooperation for the enhancement of plant biodiversity, 2001)
The Interreg II Italy-Albania Project has allowed to broaden the surface area of the Botanical garden with a view to propagating and preserving the genetic resources of the Apulian and Albanian flora and studying the re-introduction and diffusion of threatened or endangered wild and cultivated species. The activities carried out by the Botanical Garden of Lecce are performed based on the programme of 'Centro studi per la protezione e la conservazione delle specie botaniche del Mediterraneo con annesso Giardino botanico'. Indeed, working for the conservation and preservation of the plant biodiversity implies a scientific and ethical responsibility of the Botanical garden in order to pursue cultural objectives.
2. Seminar: Italo-Albanian cooperation for the enhancement of plant biodiversity, 2000/10/26-28, Tirana (Albania)